2004
DOI: 10.1038/sj.bmt.1704588
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of donor illness by stem cell transplantation: should screening be different in older donors?

Abstract: Summary:With increasing donor age, the potential of transmitting diseases from donor to recipient reaches new dimensions. Potentially transmittable diseases from donors include infections, congenital disorders, and acquired illnesses like autoimmune diseases or malignancies of hematological or nonhematological origin. While established nonmalignant or malignant diseases might be easy to discover, earlystage hematological diseases like CML, light-chain multiple myelomas, aleukemic leukemias, occult myelodysplas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 64 publications
1
48
0
Order By: Relevance
“…Transfer of leukemia by an allotransplant is reported in several leukemias including three cases of CLL. 27,28 Sala-Torra et al 28 suggested two mechanisms of donor-derived leukemia in the recipient. The first is the transfer of preleukemia cells from donor to recipient, most likely the scenario in our patient UPN 7.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Transfer of leukemia by an allotransplant is reported in several leukemias including three cases of CLL. 27,28 Sala-Torra et al 28 suggested two mechanisms of donor-derived leukemia in the recipient. The first is the transfer of preleukemia cells from donor to recipient, most likely the scenario in our patient UPN 7.…”
Section: Resultsmentioning
confidence: 99%
“…The second is the development of leukemia in normal donor stem cells. These leukemia transfer cases at the time of transplant indicate the need for careful evaluation of donors prior to graft collection, 27,29 particularly if they are relatives, older, or have positive family history of CLL.…”
Section: Resultsmentioning
confidence: 99%
“…In this respect there is no agreement on donor counselling. Niederwieser suggests determining M-proteins in both donor and recipient, but does not advocate BM investigation unless there is a family history of malignancy [15], others advocate BM aspiration in all older related donors [16]. Considering the huge number of allogeneic HSCT performed the last decades, the reported number of donor derived haematological malignancies in recipients is low, although this may increase using more sensitive techniques to detect donor derived cells and with increase of aged donor ⁄ recipient pairs [17].…”
Section: Donor Eligibilitymentioning
confidence: 99%
“…Despite the fact, that related and unrelated donors might differ for many basic characteristics (Table 1), the quality of adverse reactions associated with stem cell donation is not expected to be different between related and unrelated donors forming the rationale for a uniform donor follow-up for all types of donors. Generally, donor eligibility criteria for related donors are less strict with only a few definite criteria 20 and may vary significantly between different centers. In contrast, eligibility criteria for unrelated donors are summarized by WMDA recommendations 21 resulting in somewhat more homogenous donor selection criteria.…”
Section: Introductionmentioning
confidence: 99%